Prime Archives in Molecular Sciences 2021
DOI: 10.37247/pamol2ed.2.2021.16
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Functions of Platelets in Cancer: From Tumorigenesis to Liquid Biopsy Tool and Drug Delivery System

Abstract: Platelets contribute to several types of cancer through plenty of mechanisms. Upon activation, platelets release many molecules, including growth and angiogenic factors, lipids, and extracellular vesicles, and activate numerous cell-types, including vascular and immune cells, fibroblasts, and cancer cells. Hence, platelets are a crucial component of cell-cell communication. In particular, their interaction with cancer cells can enhance their malignancy and facilitate the invasion and colonization of distant or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 167 publications
(286 reference statements)
0
4
0
Order By: Relevance
“…This could be attributed to the nesting effect of PLT on tumor cells, and this key role made it a drug carrier for anti-cancer drugs. 30 The increased targeting ability is conducive to enhancing the killing ability to the tumor, 31 which has been verified in the later killing ability of PM encapsulated nanomaterials to tumor cells and the treatment of subcutaneous tumors in mice.
Figure 4 ( A ) CLSM images of 4T1 cells incubated with HMMD and HMMD@PG for 1 h and 3 h. The cell nuclei were stained as blue by DAPI, red was the fluorescence of DOX.
…”
Section: Resultsmentioning
confidence: 93%
“…This could be attributed to the nesting effect of PLT on tumor cells, and this key role made it a drug carrier for anti-cancer drugs. 30 The increased targeting ability is conducive to enhancing the killing ability to the tumor, 31 which has been verified in the later killing ability of PM encapsulated nanomaterials to tumor cells and the treatment of subcutaneous tumors in mice.
Figure 4 ( A ) CLSM images of 4T1 cells incubated with HMMD and HMMD@PG for 1 h and 3 h. The cell nuclei were stained as blue by DAPI, red was the fluorescence of DOX.
…”
Section: Resultsmentioning
confidence: 93%
“…Several lines of evidence support the role of platelets in the pathogenesis of several inflammatory-based diseases, including cancer [57]. In cocultures of human colon carcinoma HT29 cells and platelets, Dovizio and colleagues have reported that unstimulated platelets interact rapidly with tumor cells through the binding of platelet collagen receptors (in particular, GPVI) and tumor components such as tumor components galectin-3 [58].…”
Section: Gpvi Blockers In Tumor Metastasismentioning
confidence: 98%
“…Drug delivery systems using nanoparticles are being developed as an alternative therapeutic route for chemotherapeutic drug transport that can minimize the side effects of chemotherapy in cancer patients (146). Nanoparticles modified with P-selectintargeting agents contain the antiplatelet agent ticagrelor and the anti-inflammatory agent celecoxib.…”
Section: Perspectivesmentioning
confidence: 99%